2017
DOI: 10.7860/jcdr/2017/25807.10084
|View full text |Cite
|
Sign up to set email alerts
|

Index/Ring Finger Ratio, Hand and Foot Index: Gender Estimation Tools

Abstract: Introduction: Gender estimation from dismembered human body parts and skeletal remains in cases of mass disasters, explosions, and assaults cases is an imperative element of any medico-legal investigations and has been a major challenge for forensic scientists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
3
5
0
1
Order By: Relevance
“…The average hand index in males was 47.73 whereas the female hand index was 45.46 (Table 2). Several research investigations have been carried out on sex determination from hand dimensions (HL and HB) and also suggest the findings that males have significantly larger hand dimensions than the females counterparts (Aboul-Hagag et al 2011;Rani et al 2011;Sen et al 2011;Asha et al 2012;Ibrahim et al 2016;Varu et al 2016;Caplova et al 2017;Gupta et al 2017;Singh and Yadav 2017;Sah and Jeelani 2019). Results of the present investigation showed sex-specific mean differences in HL and HB (p<0.05) (Table 3).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The average hand index in males was 47.73 whereas the female hand index was 45.46 (Table 2). Several research investigations have been carried out on sex determination from hand dimensions (HL and HB) and also suggest the findings that males have significantly larger hand dimensions than the females counterparts (Aboul-Hagag et al 2011;Rani et al 2011;Sen et al 2011;Asha et al 2012;Ibrahim et al 2016;Varu et al 2016;Caplova et al 2017;Gupta et al 2017;Singh and Yadav 2017;Sah and Jeelani 2019). Results of the present investigation showed sex-specific mean differences in HL and HB (p<0.05) (Table 3).…”
Section: Discussionsupporting
confidence: 78%
“…The individual hand, when recovered and brought for forensic examination, can provide valuable information about the age, sex and stature of the person (Robling and Ubelaker 1997;Sen et al 2014;Jeanson et al 2017;Adelakun et al 2019;Singh et al 2019a,b). There are several research investigations, which have been undertaken to establish the relation between sex and hand dimensions in terms of HL and HB in adults (Sen et al 2011;Asha et al 2012;Uhrova et al 2015;Ibrahim et al 2016;Varu et al 2016;Caplova et al 2017;Gupta et al 2017;Singh and Yadav 2017;Sah and Jeelani 2019). The results of the present investigation showed that the male hands are significantly larger compared to the female counterparts thus showing sexual dimorphism on the basis of hand length (HL) (p<0.05) (Table 1).…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…primary aim of forensic medicine is the identification of persons [1][2][3][4][5]. Stature as an identification factor is a quantitative racial characteristic affected by factors such as nutrition, environment, gender, and genetics [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%